The Gliadin and Casein Metabolism: Synthesis of Gliadomorphin and Casomorphin and Their Biological Consequences - Mr. MD.TANZIMUR RAHMAN TAMIM, Mr. MD.TANZIMUR RAHMAN TAMIM; Rashed Ahmed (RADINKA JOURNAL OF HEALTH SCIENCE, 2025)
Gliadin (from gluten) and casein (from milk) are major dietary proteins that, upon incomplete digestion, yield biologically active opioid peptides known as gliadomorphin and casomorphin, collectively referred to as "exorphins." These peptides are increasingly recognized for their role in numerous physiological and pathological processes, particularly concerning the gut-brain axis. Methodology and Findings: This analysis describes the intricate enzymatic hydrolysis of gliadin and casein, resulting in the creation of these opioid peptides. Gliadomorphin and casomorphin are shown to cross the intestinal and blood-brain barriers, subsequently binding to opioid receptors. Their activity influences pain sensitivity, immunity, mood regulation, and mental processing. Emerging evidence suggests their involvement in disease states such as celiac disease, autism spectrum disorder (ASD), schizophrenia, and irritable bowel syndrome (IBS) through mechanisms involving altered neurotransmission, immune activation, inflammation, oxidative stress, and increased intestinal permeability. Interventions and future directions: Current and potential interventions focus on mitigating these harmful effects. Strategies include the consumption of gluten-free and casein-free diets, supplemental enzyme use (e.g., Dipeptidyl Peptidase IV/DPP-IV), modulation of the gut microbiota, and pharmacological interventions like opioid receptor antagonists and zonulin blockers. Future research necessitates the development of sophisticated diagnostic instruments and tailored nutritional regimens based on genetic and microbiome evaluations to formulate targeted therapeutic strategies. The metabolism of gliadin and casein into potent exorphins highlights a critical link between diet and the health of the gut, immune system, and brain. Further studies of gliadomorphin and casomorphin development promise novel therapeutic strategies for individuals affected by their biological activity.